Hotwater Geochemistry for Interpreting The Condition of Geothermal Reservoir, Dieng Plateau Case, Banjarnegara-Wonosobo Regency, Central Java - Ramadhan, Yuris; Channel, K.; Herdianita, N. R. (Geological Agency, 2013)
DOI:Â 10.17014/ijog.v8i2.158The researched area, located in the Dieng Plateau, is included into the Holocene Dieng Volcanic Rock Unit. The regional structure in this area is originated from the major caldera with local fault having orientation of SE - NW. Surface manifestations found in the researched area are hot springs located in Bitingan, Sileri, Siglagah, Pulosari, Kaliputih, and Sikidang. Fumaroles occur in Candradimuka and Pagerkandang and mud pools are located in Sileri and Sikidang craters. Temperatures of the hot springs ranges from 43 C to 61 C, pH of 6 - 7, and their conductivity are of 38-78 MeV. The type of hotwater is a mixture of bicarbonate, sulfate, and chloride sulfate deriving from condensation of steam. Based on a relative composition of Cl-Li-B, the hot water is originated from four different reservoirs with different rock associations, while their reservoir temperatures vary from 225 C to 300 C.